Nectar Feeding Insects on Paulownia fortunei Blossoms : Evaluating Potential Nototribic Pollinators - Singh, Arun P. (Indian Forester, 2000)
Pollination potential of different families of insects, visiting Paulownia fortunie (Scrophulariaceae) flowers nototribically for nectar feeding, was determined for the three time periods (forenoon, afternoon and evening) of the day at New Forest (78Â°00'E and 300Â°20'N), Dehra Dun, India, during its peak flowering period (22na-28th March 2000). Comparative pollination potential was determined on the basis of three parameters (i) duration of time period spent for nectar feeding, (ii) the mean height of insects dorsum from the ground, in relation to the mean vertical diameter of the corolla tube at the point of placement of anthers and stigma in it, taken for assessing its potential in making contact with the anthers (pollen) and stigma, and (iii) the presence or absence of hairs on the dorsum of the insect considered for estimating its potential to brush, carry pollen from the anthers and deposit it on the stigma. Twelve species of insects consisting representing five families [Xylocopidae (1), Bombidae (1), Apidae (3), Vespidae (3) and Syrphidae (4)], were sampled. The duration of time spent by the different families on P. fortunei blossoms varied significantly (a) in general (CD(0.5) = 1.22; Xylocoopidae > Apidae > Syrphidae > Vespidae > Bombidae), (b) with respect to the three individual time periods (CD(0.05) = 0.94; forenoon > afternoon > evening) and (iii) also with respect to the interaction between two (a) and (b) (CD(0.05) = 2.11; maximum duration of time spent by Xylocopidae, Apidae and Bombidae was in the forenoon and for Vespidae and Syrphidae it was in the afternoon], On the basis of the physical body structure and size (last two parameters) only two families [Xylocopidae (Xylocopa fenestrata Fabr.) and Bombidae (Bombus haemorrhoidalis Smith)] out of five, were determined as suitable potential pollinators of p. fortunei flowers. As, Xylocopidae spent more duration of time than Bombidae (first parameter) for nectar feeding on these blossoms, hence its role in pollination of P. fortunei was greater than Bombidae.